2001
DOI: 10.1161/hh2201.100205
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial ATP-Sensitive Potassium Channels Attenuate Matrix Ca 2+ Overload During Simulated Ischemia and Reperfusion

Abstract: Abstract-Mitochondrial ATP-sensitive potassium (mitoK ATP ) channels play a key role in ischemic preconditioning of the heart. However, the mechanism of cardioprotection remains controversial. We measured rhod-2 fluorescence in adult rabbit ventricular cardiomyocytes as an index of mitochondrial matrix Ca 2ϩ concentration ([Ca 2ϩ ] m ), using time-lapse confocal microscopy. To simulate ischemia and reperfusion (I/R), cells were exposed to metabolic inhibition (50 minutes) followed by washout with control sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

19
198
1
17

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 348 publications
(235 citation statements)
references
References 51 publications
19
198
1
17
Order By: Relevance
“…Preconditioning, a series of brief periods of ischemia and reperfusion, protects the myocardium from deleterious events associated with extended durations of ischemia and reperfusion (7)(8)(9). Cardioprotection afforded by preconditioning appears mediated, in part, by the production of oxygen radicals (35)(36)(37)(38)(39)(40) and is associated with reductions in Ca 2ϩ overload (7,(41)(42)(43) and free radical production (44) during extended periods of ischemia͞ reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Preconditioning, a series of brief periods of ischemia and reperfusion, protects the myocardium from deleterious events associated with extended durations of ischemia and reperfusion (7)(8)(9). Cardioprotection afforded by preconditioning appears mediated, in part, by the production of oxygen radicals (35)(36)(37)(38)(39)(40) and is associated with reductions in Ca 2ϩ overload (7,(41)(42)(43) and free radical production (44) during extended periods of ischemia͞ reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…51 Similarly, results from the IONA Study Group 52 and CESAR 53 clinical trials demonstrated that nicorandil, when given to patients with unstable angina, decreased cardiovascular events associated with ischemia, including a decreased incidence of arrhythmias. Murata et al 54 reported that opening of the MPT during reperfusion, secondary to cytosolic and mitochondrial calcium overload, may be primarily responsible for reperfusion-induced cellular death. They also showed that MPT opening is a reperfusion-specific phenomenon that does not occur during ischemia and that diazoxide, a mitochondrial K ATP channel opener, attenuates mitochondrial Ca 2þ loading and, consequently, MPT opening during reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…3,20,21) Although two possible mechanisms for this cardioprotective effect have been discussed, a reduction in the intracellular calcium overload by shortening the action potential duration through sarcolemmal K-ATP channel opening and the protection of mitochondrial function by opening the mitochondrial K-ATP channels, the latter has been more emphasized in recent reports because the effect of Nic on mitochondrial K-ATP channels is much stronger than that on sarcolemmal K-ATP channels. [21][22][23] Therefore, Nic is now mainly viewed as a mitochondrial K-ATP channel opener, at least at the clinical dose. In contrast, we previously documented the cardioprotective effect of Mex in an acute ischemia model.…”
Section: Discussionmentioning
confidence: 99%